Lysosomal trafficking regulator restricts intracellular growth of Coxiella burnetii by inhibiting the expansion of Coxiella-containing vacuole and upregulating nos2 expression - Wan, Weiqiang; Zhang, Shan; Zhao, Mingliang; OuYang, Xuan; Yu, Yonghui; Xiong, Xiaolu; Zhao, Ning; Jiao, Jun (Frontiers in Cellular and Infection Microbiology, 2024)
Coxiella burnetii is an obligate intracellular bacterium that causes Q fever, a zoonotic disease typically manifests as a severe flu-illness. After invading into the host cells, C. burnetii delivers effectors to regulate the vesicle trafficking and fusion events to form a large and mature Coxiella-containing vacuole (CCV), providing sufficient space and nutrition for its intracellular growth and proliferation. Lysosomal trafficking regulator (LYST) is a member of the Beige and Chediak-Higashi syndrome (BEACH) family, which regulates the transport of vesicles to lysosomes and regulates TLR signaling pathway, but the effect of LYST on C. burnetii infection is unclear. In this study, a series of experiments has been conducted to investigate the influence of LYST on intracellular growth of C. burnetii. Our results showed that lyst transcription was up-regulated in the host cells after C. burnetii infection, but there is no significant change in lyst expression level after infection with the Dot/Icm type IV secretion system (T4SS) mutant strain, while CCVs expansion and significantly increasing load of C. burnetii appeared in the host cells with a silenced lyst gene, suggesting LYST inhibits the intracellular proliferation of C. burnetii by reducing CCVs size. Then, the size of CCVs and the load of C. burnetii in the HeLa cells pretreated with E-64d were significantly decreased. In addition, the level of iNOS was decreased significantly in LYST knockout THP-1 cells, which was conducive to the intracellular replication of C. burnetii. This data is consistent with the phenotype of L-NMMA-treated THP-1 cells infected with C. burnetii. Our results revealed that the upregulation of lyst transcription after infection is due to effector secretion of C. burnetii and LYST inhibit the intracellular replication of C. burnetii by reducing the size of CCVs and inducing nos2 expression.